A new concept in European sport governance: sport as social capital - Kamberidou, I.; Patsadaras, N. (Biology of Exercise, 2007)
Social capital is a key component in understanding the relationship between European sport governing bodies and civil society. A core concept in sociology, political science, organizational behaviour and business, social capital is relatively new in the context of European sport governance. In exploring the boundaries of both sport and social capital in theory and practice, one can see sport as a form of positive social capital that promotes social cohesion, trust, social ties, etc. However, it could also be perceived as «dark» social capital since the politics of sport do not always deliver the social benefits they proclaim due to the «exclusionary» vs. inclusive factors: commercialization, doping, institutionalized gender personification, the leaky pipeline and the glass ceiling in SGBs and in competitive sports. Sport has not yet evolved into a form of social capital which can be nurtured and reproduced to raise social cohesion and eliminate social exclusions.